Engineering a Reduction of the Levelized Cost of Energy of Distributed Wind Turbines via Rotor and Control Enhancements. Issue 4 (1st May 2022) - Damiani, R; Davis, D
Abstract: Distributed wind turbines (DWTs), with rated capacity less than 100 kW, are penalized by high balance-of-system costs that lead to a high levelized cost of energy (LCOE). As a result, to contain the capital expenditure and thus LCOE, traditional designs have avoided active control systems that are standard in larger machines, e.g., active yaw and pitch control. In this paper, we present the key results of a trade-off study between larger rotor diameter, loads abatement, and simplicity in the pitch design for a typical mid-sized DWT with the overarching goal of increasing performance and decreasing LCOE. We focused on the upgrade potential for a generic downwind, passive-yaw, stall-controlled turbine model with high-speed shaft (HSS) brake and rated capacity of ∼ 60kW. A rotor and control redesign proved successful in increasing power capture through the deployment of a blade-root extender and an innovative, low-cost, independent pitch system for overspeed protection. The improvements remove the need for a mechanical brake and yield a significant decrease in LCOE. The loads in all components were kept under the target threshold by a combination of optimum blade extender length and rotor rotational velocity. The failsafe and redundant aerodynamic braking system is economical and can lend itself to retrofit applications to other turbine models.